Thunbergia laurifolia Exhibits Antifibrotic Effects in Human Hepatic Stellate Cells - Ratchadaporn Namsen (2018)
© 2017 Ratchadaporn Namsen et al. Leaves of Thunbergia laurifolia (TL) have been reported to have antioxidation, anti-inflammatory, detoxifying, and hepatoprotective effects. However, studies relating to antifibrotic activity have not been reported. Currently, there is no standard treatment for hepatic fibrosis. This study aimed to investigate the antifibrotic activity of TL in human hepatic stellate LX-2 cells. Results from cell viability and cell death assays showed that the extract at high concentrations was toxic to LX-2 cells. TL extract reversed the transformation of LX-2 cells to myofibroblast-like characteristics in response to stimulation by transforming growth factor-beta 1. This action may be associated with the effect of TL in suppressing α-SMA and collagen-I production observed by immunofluorescence study and western blot analysis. Additionally, TL extract significantly decreased MMP-9 activity which is consistent with the reduction of MMP-9, MMP-2, and TIMP-1 gene expression. The effect of TL in suppressing fibrosis may be associated with its ability to inhibit the activation of p38 MAPK and Erk1/2 kinases as examined by western blot analysis. Our study provides convincing evidence that TL possesses antifibrotic activity which may be through the suppression of TGF-β1-mediated production of MMPs, collagen-1, and α-SMA in hepatic stellate cells.